Analisis Manajemen Kemitraan Sekolah dan Industri dalam Pendidikan Vokasi: Studi pada SMK Negeri 8 Medan - Ngatmini Ngatmini; Sukarman Purba; Sahala Siallagan (Universitas Negeri Medan, 2025)
This study analyzes the partnership management between SMK Negeri 8 Medan and the Business and Industrial World based on four management functions: planning, organizing, implementing, and evaluating. The research highlights the importance of synergistic collaboration between vocational education and industry to produce competent and work-ready graduates. A mixed-methods approach was applied through interviews, observations, document analysis, and questionnaires involving 40 respondents from the school, students, and industry partners. Qualitative data were analyzed using the Miles and Huberman model, while quantitative data were processed through descriptive percentage analysis. The results show that the overall effectiveness of partnership management is in the “Good” category (average 65%). Key supporting factors include leadership commitment and teacher–student enthusiasm, while obstacles involve limited industrial partners and weak evaluation systems. Adaptive strategies include expanding partnerships, conducting industry-based teacher training, and implementing continuous evaluation. It is concluded that the effectiveness of SMK–DUDI partnerships largely depends on the school’s managerial ability to apply the four management functions integratively and adaptively to industrial dynamics.